PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SUBTEMA PELESTARIAN KEKAYAAN SUMBER DAYA ALAM DI INDONESIA - Yovani Christin Natalia Purba; Yuyun Elizabeth Patras; Yuli Mulyawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the Effect of the Application of Problem Based Learning Models Assisted by Audio Visual Media on Learning Outcomes of the Subtheme of Preservation of Natural Resources Wealth inIndonesia. This research was carried out at SDN Bantarjati 8 Bogor City for the 2022/2023 academic year. This research is with a two-class type of quasi-design experimental research. The subject of this study was class IV SDN Bantarjati 8 Bogor City consisting of 58 students. Data collection carried out to obtain learning outcomes was obtained using Pretest and Postest. This study also used the as normality test with the liliefors test. The results showed thatthe results were normally distributed because the values of both samples were smaller than the Ltable. in the experimental class group L count < L table, which is 0.048 < 0.161, in the control class L calculate < Ltable, which is 0.025 < 0.161. Furthermore, the result of the hypothesis test states that Ho is rejected and Ha (alternative hypothesis) is accepted because the value of t is calculated (4.89297) > ttable (2.00324) with dk 56 and significance level 0.05 (5%). Thus, there is an influence on the application of the Problem Based Learning model Assisted by Audio Visual Media on the learning outcomes of the subtheme of Preservation of Natural Resource Wealth in Indonesia in class IV SDN Bantarjati 8 Bogor City Even Semester of the 2022/2023 Academic Year.